Menopausal transition in multiple sclerosis: relationship with disease activity and brain volume measurements - Lorefice, Lorena; Fenu, Giuseppe; Fronza, Marzia; Murgia, Federica; Frau, Jessica; Coghe, Giancarlo; Barracciu, Maria Antonietta; Atzori, Luigi; Angioni, Stefano; Cocco, Eleonora (Frontiers in Neurology, 2023)
Background Recent evidence has shown a significant association between menopause and multiple sclerosis (MS) progression. This study investigated the possible role of menopause in influencing MS from clinical and neuroradiological perspectives. Notably, the possible association between menopause and brain atrophy has been evaluated. Materials and methods This study included women with MS whose ages ranged from 45 to 55 years. Demographic and clinical characteristics were collected, and the reproductive phase was defined as non-menopausal or menopausal based on the final menstrual period. Thus, MS activity over the past year was reported as the annualised relapse rate (ARR), and MRI activity (defined as new T2 lesions and/or the presence of gadolinium-enhancing lesions at the last MRI assessment in comparison with the MRI performed within the previous 12 months) were compared between non-menopausal women (non-MW) and menopausal women (MW). Volume measurements of the whole brain (WB), white matter (WM), grey matter (GM), and cortical GM were estimated using the SIENAX software, and the possible relationship with menopausal status was assessed by regression analysis. Results The study included 147 women with MS. Eighty-four (57.1%) were MW, with a mean age of 48.5 ± 4.3 years at menopause onset and a mean duration of menopause of 4.1 ± 1.1 years. When compared for ARR, MW reported a lower rate than the non-MW (ARR of 0.29 ± 0.4 vs. 0.52 ± 0.5; p < 0.01). MRI activity was observed in 13.1% of MW and 20.6% of non-MW (p = 0.03). Lower cortical GM volumes (578.1 ± 40.4 mL in MW vs. 596.9 ± 35.8 mL in non-MW; p < 0.01) have also been reported. Finally, multivariate analysis showed a significant association of lower ARR (p = 0.001) and cortical GM volume (p = 0.002) with menopausal status after correction for chronological age and other variables. Discussion Menopause may be an adverse prognostic factor of MS. Our preliminary results suggest that menopause may facilitate cortical GM atrophy, probably due to a decline in the neuroprotective effects of estrogen, with negative effects on MS evolution.